Empowerment of farmer organizations: case study of Farmer Managed Irrigated Agriculture Project, Sindh - Murray-Rust, Hammond; Memon, Yameen; Talpur, Mustafa (International Water Management Institute, 2001)
This paper reviews the conditions and progress towards empowerment of farmer organizations under the Farmer-Managed Irrigated Agriculture Project in the Sindh Province of Pakistan. It discusses the conditions necessary to achieve the goal of an empowered and vitalized farmer organization, the issue of legal status, skill-building activities to build the capacity of the members to manage their own affairs, and institutional issues.